SIMA-DIGI Virtual Reality-Based Disaster Mitigation - Aries Chandra Anandhita; Nugroho Ari Wibowo; Miranda Meifa; Gangga Kristin Nurfiyatul Jannah; Muhammad Adam Yulloh (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
The partner targeted by this Community Partnership Program is SD Kreatif Muhammadiyah 01 Lumajang, located in a disaster-prone area that requires further intervention. This has become a crisis situation for SD Kreatif Muhammadiyah 01 Lumajang, which can disrupt the welfare of teachers and students, resulting in anxiety and fear of natural disasters. This service aims to provide a new atmosphere and spirit in disaster mitigation learning, which will be implemented with SIMA-DIGI based on Virtual Reality in accordance with the needs of digital-based education by creating a SIMA-DIGI application based on Virtual Reality for disaster mitigation. The methods used to carry out the activities are in the form of discussions, mentoring, and training. The training, which was conducted over one week, effectively increased participants' knowledge and changed their attitudes. This was evidenced by the pre-test results, which showed that 25 students had a low level of knowledge (62.5%), 10 students had a moderate level of knowledge (25%), and 5 students had a high level of knowledge (12.5%). However, after receiving counseling and training using the SIMA DIGI Design Application, the post-test results showed a significant increase, including a drastic rise in the level of knowledge related to disaster mitigation to 87.5%. Thus, it is hoped that with the level of knowledge possessed by the students, awareness and preparedness for disasters that may occur at SD Kreatif Muhammadiyah 01 Lumajang can be improved..